2008
DOI: 10.1007/s10562-008-9580-8
|View full text |Cite
|
Sign up to set email alerts
|

High Performance of Fe–K Oxide Catalysts for Dehydrogenation of Ethylbenzene to Styrene with an aid of ppm-order Pd

Abstract: Styrene is manufactured industrially through catalytic dehydrogenation of ethylbenzene on Fe-K oxidebased catalysts. It was invented by Süd-Chemie Group that the activity of the industrial ethylbenzene dehydrogenation catalysts (Styromax) based on the oxides of Fe and K is highly promoted by the addition of small amount (hundreds ppm-order) of precious metals such as Pd. The present work is intended to elucidate the role of Pd on the Fe-K catalyst empirically by use of a periodical pulse technique from a mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 8 publications
1
16
0
Order By: Relevance
“…An isotope exchange reaction from 16 O lat to 18 O lat in the catalyst by switching H 16 2 O flow to H 18 2 O at 783 K was conducted over the Ba 0.4 Sr 0.6 Fe 0.6 Mn 0.4 O 3 − δ catalyst. We have already found that Fe–K catalyst works on a redox mechanism during EBDH (Sekine et al, 2008 ). Figure 7 presents temporary profiles of the flow rate of H 18 2 O by the time that the stable flow rate of H 18 2 O was confirmed.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…An isotope exchange reaction from 16 O lat to 18 O lat in the catalyst by switching H 16 2 O flow to H 18 2 O at 783 K was conducted over the Ba 0.4 Sr 0.6 Fe 0.6 Mn 0.4 O 3 − δ catalyst. We have already found that Fe–K catalyst works on a redox mechanism during EBDH (Sekine et al, 2008 ). Figure 7 presents temporary profiles of the flow rate of H 18 2 O by the time that the stable flow rate of H 18 2 O was confirmed.…”
Section: Resultsmentioning
confidence: 92%
“…We previously investigated the reaction mechanism of EBDH with steam over the industrial potassium promoted the iron catalyst (Fe–K) catalyst, and found for the first time that oxidative dehydrogenation of EBDH (Equation 2) proceeded on the Fe–K catalyst and H 2 O can regenerate the consumed lattice oxygen in the catalyst (Equation 3) (Sekine et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…When producing RM, a potassium doped iron oxide catalyst is often used. It was developed for industrial production reactions and is studied extensively due to its complexity and usefulness [34][35][36]. For these kinds of catalysts a flux of highly excited potassium Rydberg species have been proven by field ionization method, and this flux corresponded to the catalyst activity [37].…”
Section: Theory and Working Principle Of Rm Productionmentioning
confidence: 99%
“…Calibration curves of each analyte were constructed using relative response factor against concentration of analyte from gas chromatography signals of prepared mixtures of known composition and used for estimating the percentage of each analyte in the liquid products. In this analysis, tetralin was used as an internal standard substance [26]. A typical calibration plot for determining the percentage of ethylbenzene composition in the mixture of products is shown in Fig.…”
Section: Catalytic Activity Studiesmentioning
confidence: 99%